Alleviative effects of pinostrobin against cadmium-induced renal toxicity in rats by reducing oxidative stress, apoptosis, inflammation, and mitochondrial dysfunction - Ijaz, Muhammad Umar; Shahzadi, Sabahat; Hamza, Ali; Azmat, Rabia; Anwar, Haseeb; Afsar, Tayyaba; Shafique, Huma; Bhat, Mashooq Ahmad; Naglah, Ahmed M.; Al-Omar, Mohamed A.; Razak, Suhail (Frontiers in Nutrition, 2023)
Cadmium (Cd) is a toxic heavy metal that is ubiquitous in the environment, has harmful effects on human as well as animal health. Pinostrobin (PSB), a bioactive natural flavonoid isolated from Boesenbergia rotunda, that possesses several pharmacological activities such as anti-inflammatory, anticancer, anti-oxidant, and anti viral. This investigation was intended to assess the therapeutic potential of PSB against Cd-instigated kidney damage in rats. 48 Sprague Dawley rats were distributed into 4 groups and designed as control, Cd (5 mg/kg), Cd + PSB (5+10mg/kg) and PSB (10mg/kg) supplemented group for 30 days. Cd exposure resulted in decreased catalase (CAT), glutathione reductase (GSR), superoxide dismutase (SOD) as well as glutathione peroxidase (GSH-PX) activities, whereas, esclated the levels of ROS along with MDA. Cd exposure also caused a substantial upsurge in the urea, kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL) as well as creatinine levels besides a noticeable decline was noticed in creatinine clearance. Moreover, Cd exposure considerably augmented the levels of inflammatory indices, Interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6), nuclear factor kappa-B (NF-κB), inducible nitric oxide synthase (iNOS) along with cyclooxygenase-2 (COX-2) activity. Cd treatment decreased anti-apoptotic marker (Bcl-2) expression besides, increasing apoptotic markers (Bax & Caspase-3). Furthermore, Cd treatment substantially reduced the TCA cycle enzymes activity such as alpha-ketoglutarate dehydrogenase, succinate dehydrogenase, malate dehydrogenase as well as isocitrate dehydrogenase. Besides, mitochondrial electron transport chain enzymes, succinate-dehydrogenase, NADH dehydrogenase, cytochrome c-oxidase as well as coenzyme Q-cytochrome reductase activities were also decreased following Cd exposure. PSB administration substantially lowered the mitochondrial membrane potential while significantly induced histological damages. However, PSB treatment significantly reduced the Cd-mediated renal damage in rats. Thus, the recent investigation suggested that PSB has ameliorative potential against Cd-instigated renal dysfunction in rats.